2017
DOI: 10.1556/004.2017.040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arginine and trehalose on post-thawed bovine sperm quality

Abstract: The present study was conducted to examine the protective role of arginine and trehalose on post-thaw bull sperm and oxidative stress parameters. Five ejaculates for each bull were used in the study. Each ejaculate, split into three equal aliquots and diluted at 37 °C with base extenders containing 2 mM arginine, 25 mM trehalose and no antioxidant (control) was cooled to 5 °C and then frozen. Frozen straws were thawed in a water bath for evaluation. Supplementation of the semen extender with arginine decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
(39 reference statements)
0
8
0
Order By: Relevance
“…Another supplement that has shown promising results in frozen semen is trehalose; several studies have shown that this disaccharide positively affects post‐thawing semen motility, acrosomal and plasma membrane integrity and overall viability (Hu et al, ; Shiva, Jagan, & Atreja, ), as well as increasing mitochondrial activity and keeping DNA intact (Öztürk et al, ). The effect of trehalose can be explained by its ability to promote dehydration (Aisen, Quintana, Medina, Morello, & Venturino, ) or interact with membrane biomolecules (Bucak et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Another supplement that has shown promising results in frozen semen is trehalose; several studies have shown that this disaccharide positively affects post‐thawing semen motility, acrosomal and plasma membrane integrity and overall viability (Hu et al, ; Shiva, Jagan, & Atreja, ), as well as increasing mitochondrial activity and keeping DNA intact (Öztürk et al, ). The effect of trehalose can be explained by its ability to promote dehydration (Aisen, Quintana, Medina, Morello, & Venturino, ) or interact with membrane biomolecules (Bucak et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Öztürk et al studied the effect of arginine and trehalose on bovine sperm samples in their study. Trehalose showed higher (50.5% subjective, 64.7% CASA) motility than arginine (29% subjective, 12.2% CASA) when compared to the control group [71]. Uysal and Bucak studied rapid (10°C/min from 5 to −25°C, 50°C/min from −25 to −130°C) and slow (0.5°C/min from 5 to −25°C, 50°C/min from −25 to −130°C) cooling rates with different doses of trehalose (0, 50, 100, 150 mM), and investigated sperm motility, survivability, membrane integrity, and morphologically abnormal sperm rates after thawing.…”
Section: Non-penetrating Cryoprotectantsmentioning
confidence: 78%
“…Ethylene glycol and NGF had the most unfavorable impacts on total and progressive motility, respectively ( Table 4 ), while glycerol and trehalose had the most favorable results. The cryoprotective effects of glycerol and trehalose on the motility parameters of bull sperm have been shown in different studies [ 24 , 25 , 26 , 27 , 28 ]. In contrast, Foote et al [ 29 ] discovered that trehalose did not increase the fertility of bull sperm frozen in whole milk.…”
Section: Resultsmentioning
confidence: 99%
“…The correlation coefficients between the manifest and corresponding latent variables were lower than 0.5 for the melatonin variable in the antioxidant block, the tris variable in the basic compounds block, and the egg yolk variable in the extracellular protectant block ( Figure 7 ). Öztürk [ 27 ] pointed out that freezing extenders containing modest concentrations of cryoprotectant combined with trehalose reduced the sensitivity of ram spermatozoa to cryopreservation and osmotic damage.…”
Section: Resultsmentioning
confidence: 99%